WASTE MANAGEMENT IN THE EUROPEAN UNION - Bugarski, Tatjana; Tubić, Bojan; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Over the past few decades, there has been significant concern about the impact of waste on the environment, and accordingly, the former European Communities and the European Union have adopted a number of environmental regulations. Inadequate waste management has led to numerous cases of pollution of land and groundwater, which jeopardizes the natural functioning of the ecosystem and the health of the population that is exposed to pollution. The EU Sustainable Development Strategy identifies the prevention of waste generation and proper management of it as one of its main priorities. The need for waste management is clearly emphasized, in which way the minimum risk of endangering the lives and health of people and the environment is minimized. The aim of this paper is to present the most important EU regulations on waste management, as well as to analyze relevant case law.